EVALUASI PRODUKTIVITAS CV. BESTONE INDONESIA DENGAN METODE POSPAC DAN PERFOMANCE PRISM - Hamdan Fauzan; Ari Zaqi Al-Faritsy (Jurnal Cakrawala Ilmiah, 2023)
CV Bestone Indonesia is a company engaged in the production sector of natural stone cutting, which utilizes natural stone to make ceramics and other furturistic ornaments. CV. Bestone Indonesia is located in Tegal Rejo, Jatingarang, Weru, Sukoharjo. From the results of the partial POSPAC productivity calculations from January 2022 to December 2022 it shows that the value of productivity from month to month has decreased and increased (fluctuations). The highest productivity ratio results were obtained for the sales indicator in the October 2022 period with a productivity ratio of 21.277 and a productivity index of 110.64%, for the lowest productivity measurement Also the Sales indicator in the June 2022 period with a productivity ratio value of 19.608 and a productivity index of 88.24% . Things that can be done by companies to increase sales productivity based on the Performance Prism analysis is to maintain reciprocal relationships with consumers (Customer relationship). Customer relationship is a marketing strategy that is useful for maintaining consumers, customers, and also clients so they don't switch to competitors' businesses. Through well-maintained customer relationships, the business being run will have more potential to get repeat purchases from customers.